Political Geography - Martin Ira Glassner (New York(State): John Wiley & Sons, 1993)
The present work contains a number of new features. Naturally, it has been thoroughly updated. Chapters 1, 18 and 19 have been extensively rewritten, and there is a new Chapter 17 on indigenous peoples. Several new sections appear, notably those on international peacekeeping operations, the Arctic, contemporary State practice in marine affairs, the proposed New World Information and Communication Order and New International Economic Order, and the United States outer continental shelf. There are 15 new maps and numerous new graphs, photographs, and other illustrations.
(NP(B/11469s
+Maps
+Photos
Keywords: world -- regional states -- international law -- economic integration